Isolation and Molecular Characterization of Legume Microorganisms Used in Yogurt FermentationYogurt is generally defined as a fermented dairy product which is produced by using the symbiotic cultures of Streptococcus thermophilus and Lactobacillus delbrue - Çay, Mesut; Oğuzkan, Sibel Bayıl; Kılıç, İbrahim Halil (European Journal of Applied Sciences, 2021)
Yogurt is generally defined as a fermented dairy product which is produced by using the symbiotic cultures of Streptococcus thermophilus and Lactobacillus delbrueckii subsp. bulgaricus. The positive effects of yogurt and other similar fermented dairy products on human diet and health continue to be proven and this has led to increased yogurt consumption in the world which in turn demands more production. In addition, there are works in progress to improve yogurt quality and produce yogurt with various specifications using newly developed techniques. In this study, four distinct types of legume (lentil, bean, cow pea and broad bean) were used to ferment yogurt from milk of without UHT. Yogurt samples were diluted and then each sample was transferred to a M17 Agar medium and bacteria were isolated from these samples. Fresh pure cultures were obtained. The new generation sequence was subjected to a 16s rRNA array analysis and characterization using MALDI-TOF methods. It was determined that the bacteria in the yogurt which were produced were Streptococcus thermophilus and Lactobacillus delbrueckii subsp. bulgaricus. In accordance with the data obtained, the bacteria which was reproduced in the MRS and M17 mediums proved to be preliminary examples of cultivated bacteria which can be utilized in commercial yogurt production.